Changes in allelic frequency over time in European bread wheat (Triticum aestivum L.) varieties revealed using DArT and SSR markers - Orabi, Jihad; Jahoor, Ahmed; Backes, Gunter (Euphytica, 2014)
A collection of 189 bread wheat landraces and cultivars, primarily of European origin, released between 1886 and 2009, was analyzed using two DNA marker systems. A set of 76 SSR markers and ~7,000 DArT markers distributed across the wheat genome were employed in these analyses. All of the SSR markers were found to be polymorphic, whereas only 2,532 of the ~7,000 DArT markers were polymorphic. A Mantel test between the genetic distances calculated based on the SSR and DArT data showed a strong positive correlation between the two marker types, with a Pearson’s value (r) of 0.66. We assessed the genetic diversity and allelic frequencies among the accessions based on spring- versus winter-wheat type as well as between landraces and cultivars. We also analyzed the changes in genetic diversity and allelic frequencies in these samples over time. We observed separation based on both vernalization type and release date. Interestingly, we detected a decrease in genetic diversity in wheat accessions released over the period from 1960 to 1980. However, our results also showed that modern plant breeding have succeeded in maintaining genetic diversity in modern wheat cultivars. Studying allelic frequencies using SSR and DArT markers over time revealed changes in allelic frequencies for a number of markers that are known to be linked to important traits, which should be useful for genomic screening efforts. Monitoring changes in the frequency of molecular DNA markers over time in wheat cultivars may yield insight into alleles linked to important traits that have been the subject of positive or negative selection in the past and that may be useful for marker-assisted breeding programs in the future.